Neuroprotective and Antioxidant Effect of Ginkgo biloba Extract Against AD and Other Neurological Disorders - Singh, Sandeep Kumar; Srivastav, Saurabh; Castellani, Rudolph J.; Plascencia-Villa, Germán; Perry, George (Neurotherapeutics, 2019)
Alzheimer's disease (AD) is the most common progressive human neurodegenerative disorder affecting elderly population worldwide. Hence, prevention of AD has been a priority of AD research worldwide. Based on understanding of disease mechanism, different therapeutic strategies involving synthetic and herbal approaches are being used against AD. Among the herbal extract, Ginkgo biloba extract (GBE) is one of the most investigated herbal remedy for cognitive disorders and Alzheimer's disease (AD). Standardized extract of Ginkgo biloba is a popular dietary supplement taken by the elderly population to improve memory and age-related loss of cognitive function. Nevertheless, its efficacy in the prevention and treatment of dementia remains controversial. Specifically, the added effects of GBE in subjects already receiving “conventional” anti-dementia treatments have been to date very scarcely investigated. This review summarizes recent advancements in our understanding of the potential use of Ginkgo biloba extract in the prevention of AD including its antioxidant property. A better understanding of the mechanisms of action of GBE against AD will be important for designing therapeutic strategies, for basic understanding of the underlying neurodegenerative processes, and for a better understanding of the effectiveness and complexity of this herbal medicine.